2021
DOI: 10.1021/acsomega.1c00699
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Free Stabilization of Aqueous Graphene Dispersions Using Starch as a Dispersing Agent

Abstract: Attention to graphene dispersions in water with the aid of natural polymers is increasing with improved awareness of sustainability. However, the function of biopolymers that can act as dispersing agents in graphene dispersions is not well understood. In particular, the use of starch to disperse pristine graphene materials deserves further investigation. Here, we report the processing conditions of aqueous graphene dispersions using unmodified starch. We have found that the graphene content of the starch–graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Iqbal et al [ 167 ] recorded high stability and better colloidal stability of iron oxide nanoparticles at high temperature (120 °C) via electrosteric stabilization using poly(AMPS-co-AA) copolymer. Zhao et al [ 168 ] reported the good stability of PNF composed of starch and graphene nanoparticles. Similarly, Vasconcelos et al [ 169 ] observed that ethylenediamine-modified graphene oxide nanoparticles exhibited good stability properties after aging for 90 days, with 146% higher viscosity over HPAM.…”
Section: Binary Combination Of Polymers and Other Additives For Eormentioning
confidence: 99%
“…Iqbal et al [ 167 ] recorded high stability and better colloidal stability of iron oxide nanoparticles at high temperature (120 °C) via electrosteric stabilization using poly(AMPS-co-AA) copolymer. Zhao et al [ 168 ] reported the good stability of PNF composed of starch and graphene nanoparticles. Similarly, Vasconcelos et al [ 169 ] observed that ethylenediamine-modified graphene oxide nanoparticles exhibited good stability properties after aging for 90 days, with 146% higher viscosity over HPAM.…”
Section: Binary Combination Of Polymers and Other Additives For Eormentioning
confidence: 99%
“…[14] In recent years, graphene nano-sheets, a 2D network of sp 2 -hybridized carbon atoms in a hexagonal configuration, have captured immense attention as an alternative conductive ink owing to its exceptional combination of mechanical, thermal, optical, and electronic properties. [14][15][16][17][18][19][20] Formulating inkjet printable graphene ink is generally challenging since the inkjet printing method requires the ink to have specific range of values for the properties such as flake size, surface energy, viscosity, and density. [6,14] The inks mostly require additional surfactants and binders for stabilization that must be removed after the printing process by post-treatment methods in order to attain the desired properties.…”
Section: Highly Conductive Films By Rapid Photonic Annealing Of Inkje...mentioning
confidence: 99%
“…[3,[7][8][9][10][11][12][13] However, the actual material choice of the ink for a particular application is dictated by several factors including nanoparticles as dispersing agent. [19] Starch is produced from plant-based sources on a large scale and used in numerous industrial sectors, such as food, papermaking, and pharmaceuticals. [24] The abundant, biodegradable, and renewable nature of starch paves the way for production of eco-friendly graphene ink.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations